(untitled) ("Temas Sociais" Journal, 2022)
It is a reality that some trans people experience obstructions in the fulfillment of human rights and are often deprived of a full compliance in the exercise of citizenship. There are organizations that promote the full civic participation of these people, urging the States to create policy that involve, promote, and assist the constraints that these people face nowadays. The Social Sciences have strengthened collaborative research in the debunking of prejudice, and Social Work emerges as a bridge in the devolution of citizenship and the empowerment of trans people, having as reference the values of Human Rights. Social workers are key allies in efforts to ensure well-being and equity for people with non-normative gender identity. These professionals are committed in promoting policies and programs that affirm, support, and value individuals and communities, ever committed to both social and justice inclusion.